PEMBERDAYAAN MASYARAKAT SEBAGAI APLIKASI GERAKAN MASYARAKAT CERDAS MENGGUNAKAN OBAT (GEMA CERMAT) - Maria Hilaria; Yorida F Maakh (P3M Universitas Aisyiyah Surakarta, 2019)
The use of drugs is said to be rational if the patient receives a drug that is in accordance with his clinical needs, in doses according to his needs and in an adequate period of time. One of the efforts to increase public knowledge in order to be able to carry out safe and appropriate replication with the activities of Gema Cermat (Smart Society Using Medicines Movement. The target and outcome of community service carried out through over-the-counter self-medication training will be produced by the community, especially hamlet 01, Baumata village has the knowledge and skills in choosing to choose over-the-counter drugs for self-medication. The method of implementing the activity is a form of socialization using a two-way interactive method, namely how to provide information dissemination carried out by giving information from students and lecturers on material translation using power point, giving leaflet introduction to drugs and giving samples in the form of drugs that are classified as over-the-counter drugs. Before the education level of knowledge is sufficient (38%) and less 62%. After education, the level of knowledge is good 11%, enough 73% and less 16%. There was an increase in people's knowledge about drugsThe use of drugs is said to be rational if the patient receives a drug that is in accordance with his clinical needs, in doses according to his needs and in an adequate period of time. One of the efforts to increase public knowledge in order to be able to carry out safe and appropriate replication with the activities of Gema Cermat (Smart Society Using Medicines Movement. The target and outcome of community service carried out through over-the-counter self-medication training will be produced by the community, especially hamlet 01, Baumata village has the knowledge and skills in choosing to choose over-the-counter drugs for self-medication. The method of implementing the activity is a form of socialization using a two-way interactive method, namely how to provide information dissemination carried out by giving information from students and lecturers on material translation using power point, giving leaflet introduction to drugs and giving samples in the form of drugs that are classified as over-the-counter drugs. Before the education level of knowledge is sufficient (38%) and less 62%. After education, the level of knowledge is good 11%, enough 73% and less 16%. There was an increase in people's knowledge about drugs